2010
DOI: 10.1159/000315109
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Functions of Sphingosine-1-phosphate

Abstract: The biologically active sphingolipid sphingosine-1-phosphate (S1P) plays key functions in the immune, inflammatory, and cardiovascular systems. In the vasculature, S1P and its receptors are involved in vessel morphogenesis and angiogenesis during embryonic development and in the adult organism both under normal and pathological conditions. Via its actions on endothelial and smooth muscle cells, S1P regulates arterial tone, vascular permeability, and tissue perfusion. Elevated local S1P levels during inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(68 citation statements)
references
References 96 publications
1
67
0
Order By: Relevance
“…The SphK activity, detected in endothelial cells upon LPS plus S1P treatment, suggests the involvement of the S1P-SphK axis, in addition to an interplay at the ERK, which has been reported to act upstream of SphK-1 (39). However, the contribution of TNF-ainduced endogenous S1P could not be ruled out because LPSinduced TNF-a expression and TNF-a-mediated activation of SphK-1-S1P signaling has been shown (2,11). The lack of TNF-a induction observed in cytokine arrays after 8 h of treatment with LPS plus S1P may suggest that the previous observations of LPS on TNF-a could be a secondary response that would not explain the short-term responses we report in this study with LPS plus S1P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SphK activity, detected in endothelial cells upon LPS plus S1P treatment, suggests the involvement of the S1P-SphK axis, in addition to an interplay at the ERK, which has been reported to act upstream of SphK-1 (39). However, the contribution of TNF-ainduced endogenous S1P could not be ruled out because LPSinduced TNF-a expression and TNF-a-mediated activation of SphK-1-S1P signaling has been shown (2,11). The lack of TNF-a induction observed in cytokine arrays after 8 h of treatment with LPS plus S1P may suggest that the previous observations of LPS on TNF-a could be a secondary response that would not explain the short-term responses we report in this study with LPS plus S1P.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the pathophysiological role of S1P, even though it has been suggested that S1P could explain in part the atheroprotective effects of highdensity lipoproteins, both S1P-mediated anti-atherogenic and proatherogenic effects have been reported in the vascular system (8)(9)(10). In endothelial cells, S1P promotes the expression of adhesion molecules associated with angiogenesis and atherosclerosis processes and the expression of inflammation-related genes, although it also promotes anti-atherogenic effects (8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Among lysosphingolipids, S1P is particularly interesting as this bioactive lipid plays key roles in vascular biology (Lucke and Levkau 2010). More than 90 % of circulating sphingoid base phosphates are found in HDL and albumin-containing fractions (Table 3) (Kontush and Chapman 2012).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…S1P carried by HDL is believed to regulate arterial tone, vascular permeability, and tissue perfusion. During inflammation it induces endothelial adhesion molecules and recruits inflammatory cells, and furthermore it activates a negative feedback loop that consecutively decreases vascular leakage by improving the endothelial barrier function and preventing cytokine-induced leukocyte adhesion (Garcia et al 2001;Lucke and Levkau 2010;Takeya et al 2003).…”
Section: Mechanisms Under Physiological Conditionsmentioning
confidence: 99%